Successful factors of 540° Dwihuryeochagi in taekwondo - Yoo, S. H.; Ryu, J. S.; Park, S.-K.; Yoon, S.-H.; Gil, H.-J.; Kim, J.-N.; Park, S.-H. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of our study was to provide fundamental information about success factors of 540° Dwihuryeochagi in Taekwondo. Twenty Taekwondo athletes who participated in the 2012 Taekwondo Kyukpa Wang (breaking king) championship: ten successful athletes (S, age: 23.1±1.6 yrs, height: 171.0±3.5 cm, body mass: 66.4±7.1 kg) and ten failed athletes (F, age: 22.3±1.8 yrs, height: 172.1±5.4 cm, body mass: 64.4±4.2 kg) were selected. Three-dimensional motion analysis using a system of 3 video cameras with a sampling of 60 fields/s was performed during the competition of 540° Dwihuryeochagi. Based on the findings, it is concluded that success factors of 540° Dwihuryeochagi were horizontal velocity of COM during P1, vertical velocity of COM during P2, and the time, kick distance, velocity and angle of lower extremities of P3-P4.